Model DeLone and McLean Dalam Mengukur Kesuksesan E-Akreditasi Lembaga Kesejaterahan Sosial - Subandi; Wiharto, Yudi; Kusdiarto, Djati (Journal Software, Hardware and Information Technology, 2024)
This research adapts the Delone and McLean model which was originally used to measure the success of information systems into a framework that is appropriate to the context of E-Accreditation. The model consists of three main dimensions, namely system quality, information quality, and user satisfaction. Relevant variables in the context of E-Accreditation will be identified and integrated into this model. This research aims to develop and test the Delone and McLean model in the context of measuring the success of E-Accreditation of Social Welfare Institutions. E-Accreditation is a system used by social welfare institutions to measure and ensure the quality of the services they provide to the community. The success of E-Accreditation is very important in increasing the effectiveness and efficiency of these institutions in fulfilling their duties. The research method that will be used is a survey of E-Accreditation users in social welfare institutions. Data will be analyzed using appropriate statistical techniques to test the relationship between variables in the adapted Delone and McLean model. The results of this research can provide a better understanding of the factors that influence the success of E-Accreditation in the context of social welfare institutions.